Pengembangan Model Termal Rumah Nelayan Berbasis data Lapangan di Pantai Dusun Karama Tengah Kabupaten Takalar - Andi Ahmad Fauzan Bachtiar; Muhammad Ikhsan Andi (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2026)
This study aims to analyze the thermal performance of fishermen's residential buildings through the integration of field measurement data with computer simulation modeling. This approach is carried out to identify microclimate variables, such as air temperature and humidity, in order to achieve adaptive thermal comfort standards for coastal communities. The data collection method was carried out for five consecutive days at the peak of the rainy season to map extreme microclimatic fluctuations in the coastal environment. The results of these measurements are then validated by software simulations to ensure the accuracy of the data to actual conditions in the field. Further analysis was carried out by evaluating the influence of building envelope materials on heat transmission to formulate effective heat mitigation strategies. This finding is expected to be a reference in the development of vernacular home design that is able to optimize air circulation and maintain the thermal stability of the interior passively. In addition, this study also examines the correlation between the orientation of the building and the direction of the sea breeze in increasing the effectiveness of natural ventilation in residential areas. This mapping of thermal characteristics provides in-depth insights into how design adjustments to architectural elements can significantly affect building performance in coastal areas with high humidity. The integration of this empirical data allows the development of thermal prediction algorithms that are specific to the typology of fishermen's habitation, so that it is able to provide targeted temperature mitigation design solutions for coastal tropical climates.